Theoretical analysis of the structural, electronic, optical and thermodynamic properties of trigonal and hexagonal Cs3Sb2I9 compound - Saadi Berri (Université de M'sila, 2020)
The structural, electronic, optical and thermodynamic properties of Cs3Sb2I9 compound with 0-D dimer form (hexagonal SP; P63=mmc, no. 194) and the 2-D layered form (trigonal SP; P3 m1, no. 164) phases have been investigated and reported using both FP-LAPW and PP-PW methods. Besides, the thermodynamic properties of the materials of interest have been studied using the quasi-harmonic Debye model accommodating the lattice vibrations e ects. The obtained lattice parameters for dimer and layered phase reveal very good accord with experiment. The computed electronic band structures show that in the dimer phase the material of interest is an indirect band-gap (k{􀀀) semiconductor, whereas it is a direct band-gap (􀀀{􀀀) in the layered phase. The semiconducting material Cs3Sb2I9 of interest was found to be stable against volume change of 0 to +14%. Moreover, the optical properties of the material in question are also examined and discussed. The e ect of pressure and temperature on the studied properties is found to be highly e ective in tuning some of the macroscopic properties of the compound in question